Investigation of novel thermoelectric refrigeration systems - Ma, Xiaoli (2004)
Concern over global warming and depletion of the ozone layer has stimulated research to develop cooling methods that do not employ environmentally damaging working fluids such as CFCs and HCFCs. Two methods that have been considered are absorption and thermoelectric `Peltier' cooling systems. Absorption systems, using H20/LiBr have the advantage of being able to use low-grade waste heat. However, the large volume, high capital cost and low performance of these systems have inhibited their widespread application.